The grand promenade - EMST, Athens (Athene : EMST (National Museum of Contemporary Art) Athens, 2006)
Althamer, Pawel ; Amer, Ghada ; Angelidakis, Andreas ; Antoni, Janine ; Ataman, Kutlug ; Barclay, Per ; Blum, Michael ; Boltanski, Christian ; Büchler, Pavel ; Caniaris, Vlassis ; Elkoury, Fouad ; Hadjimichalis, George ; Hill, Gary ; Hirschhorn, Thomas ; Kabakov, Ilya & Emilia ; Kami, Y.Z. ; Kapoor, Anish ; Karamustafa, Gülsün ; Khedoori, Toba ; Kounellis, Jannis ; Laib, Wolfgang ; Lambri, Luisa ; Manetas, Miltos ; Mehretu, Julie ; Neto, Ernesto ; Otto-Knapp, Silke ; Paci, Adrian ; Philipsz, Susan ; Pikionis, Dimitris ; Plessas, Angelo ; Rabah, Khalil ; Roden, Steve ; Rückriem, Ulrich ; Sierra, Santiago ; Solakov, Nedko ; Syberberg, Hans-Jürgen ; Theodorou, Lina ; Tsantila, Evanthia ; Velonis, Kostis ; Whiteread, Rachel ; Wulffen, Amelie von ; Xagoraris, Zafos ; Xenou, Vana ; Yu Hong
Engels, Grieks
Published on the occasion of the exhibition "The grand promenade" at EMST (National Museum of Contemporary Art) in Athens, 17.07.2006 - 29.09.2006
boek